2020
DOI: 10.3233/jhd-200418
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Interventions for People with Huntington’s Disease: A Call to Arms

Abstract: Background: Although Huntington’s disease (HD) can cause a wide range of psychological difficulties, no review has ever been carried out on the range of psychological interventions adopted with this population. Objective: To scope the literature on psychological interventions for psychological difficulties in people affected by HD. Methods: A systematic scoping review was performed across MEDLINE, PsycINFO, CINAHL, Academic Search Ultimate, and Cochrane Library up to 1 March 2020. Results: From an initial retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 106 publications
0
29
0
5
Order By: Relevance
“…Even though the importance of psychological approaches in people with PD has received more recognition compared to other neurodegenerative conditions, such as Huntington’s disease and motor neuron disease (Anestis, Eccles, Fletcher, French, & Simpson, 2020; Simpson et al, 2019; Zarotti, Dale, Eccles, & Simpson, 2020; Zarotti, Mayberry, Ovaska‐stafford, Eccles, & Simpson, 2020), the current literature around psychological interventions for PD is mainly characterized by low‐level and/or underpowered studies, and more comprehensive high‐powered RCTs are urgently needed. In addition, since only five studies out of 56 involved samples with a mean age lower than 60, all of which showed promising results (Berardelli, Pasquini, Bloise, et al, 2015; Dreisig et al, 1999; Lundervold et al, 2013; Okai et al, 2013; Sproesser et al, 2010), further investigations are required to explore the impact of psychological interventions in younger patients, in particular due to the potentially lower severity of cognitive and motor difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the importance of psychological approaches in people with PD has received more recognition compared to other neurodegenerative conditions, such as Huntington’s disease and motor neuron disease (Anestis, Eccles, Fletcher, French, & Simpson, 2020; Simpson et al, 2019; Zarotti, Dale, Eccles, & Simpson, 2020; Zarotti, Mayberry, Ovaska‐stafford, Eccles, & Simpson, 2020), the current literature around psychological interventions for PD is mainly characterized by low‐level and/or underpowered studies, and more comprehensive high‐powered RCTs are urgently needed. In addition, since only five studies out of 56 involved samples with a mean age lower than 60, all of which showed promising results (Berardelli, Pasquini, Bloise, et al, 2015; Dreisig et al, 1999; Lundervold et al, 2013; Okai et al, 2013; Sproesser et al, 2010), further investigations are required to explore the impact of psychological interventions in younger patients, in particular due to the potentially lower severity of cognitive and motor difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Intact metacognitive insight despite (impaired) cognitive performance in premanifest and early-HD is of clinical interest because it may be used to enhance subjective well-being and mental health (5). HD causes a wide range of psychological difficulties, but the literature on psychological interventions for people affected by HD is extremely limited (30)A recent feasibility study has shown that mindfulness-based cognitive therapy (which exploits metacognition) can be beneficial to individuals with premanifest HD (31). Our finding that early-HD gene-carriers retain good metacognitive insight further indicates that psychological therapies designed to apply this skill positively, may help maintain psychological well-being following a genetic diagnosis of HD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is a high prevalence of spiritual and existential distress (hopelessness, concern with death and dying, suicidality), 10,11 which is more salient than in other neurological diseases 12 . However, there are no evidence‐based palliative care models or psychotherapeutic interventions that can ameliorate these distressing symptoms among people with the HD gene mutation 9,13,14 …”
Section: Introductionmentioning
confidence: 99%
“…Despite the multitude of PROs, the non‐motor ones (e.g., cognition or depression) seem to be more potent contributors to HRQOL scores than do the motor impairments, and perhaps more so in the earlier disease stages. 7 , 8 , 9 Additionally, there is a high prevalence of spiritual and existential distress (hopelessness, concern with death and dying, suicidality), 10 , 11 which is more salient than in other neurological diseases. 12 However, there are no evidence‐based palliative care models or psychotherapeutic interventions that can ameliorate these distressing symptoms among people with the HD gene mutation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation